Keberadaan Tari Rantak Dalam Masyarakat Pencinta Seni Di Sumatera Barat: Antara Mentradisi Dan Anggapan Sebagai Tari Tradisional - Lola Murnianti; Indrayuda Indrayuda; Darmawati Darmawati (FBS Universitas Negeri Padang, 2019)
This article aims to disclose and describe the Minangkabau society about the reasons consider dance dance Rantak as the Minangkabau traditions and looking for answers as to why the Rantak can dance mentradisi in Minangkabau society. This type of research in the study was qualitative research with a descriptive method. The main instrument in the penelitia this is the researcher himself, and assisted with the supporting instruments such as stationery, tape and camera rekorder photos. Types of data using primary data and secondary data. The technique of data collection is done with the study of librarianship, observation observation, interview and documentation. And the steps undertaken to analyze data is grouped data, analyze data, describe the data and create reports. The results showed that among the general public is currently not many know the existence of the dance Rantak dance berakarkan to creations that dance traditions. At the moment it is rare in Rantak dance pull again by society because of the lack of public knowledge about the existence of the dance Rantak, the influence of modern art, education, culture and the lack of demand from the public for showing that Rantak Dance on its own. But the dance Rantak been mentradisi among the Minangkabau people, dance is often bring in at that point in the race events, extracurricular and disekolah-sekolah festival.